The Influence of Natural and Climatic Conditions on the Architectural Development of Cities (Journal of Science-Innovative Research in Uzbekistan, 2025)
This paper explores the significant impact of natural and climatic conditions on the architectural development of cities. It highlights how factors such as temperature, humidity, precipitation, topography, and natural disasters influence the choice of building materials, urban planning, and structural design. The study examines various regional examples to show how architects and urban planners adapt to environmental constraints to create sustainable, functional, and climate-responsive urban environments. The analysis underscores the importance of incorporating ecological and climatic considerations in the architectural strategies of modern cities.